2013
DOI: 10.1590/abd1806-4841.20132145
|View full text |Cite
|
Sign up to set email alerts
|

Differences in age and topographic distribution of the different histological subtypes of basal cell carcinoma, Taubaté (SP), Brazil

Abstract: BACKGROUND Basal cell carcinoma is the most common form of cancer in humans. OBJECTIVES To identify the epidemiology of basal cell carcinoma in Taubaté-SP and verify a possible association between topography and the different histological subtypes of this tumor. METHODSThis was a cross-sectional study conducted at The University Hospital of Taubaté between 01/01/08 and 12/31/09. The study included patients with a confirmed diagnosis of basal cell carcinoma, of both genders, without age restrictions. The variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
7
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
8
7
1
1
Order By: Relevance
“…In SCC, the head and neck accounted for a larger proportion of lesions for men than women, and the lower limbs were affected more commonly (in our series exclusively) in women, justifying literature data [3,9,15,16,27]. In BCC, the trunk, especially the back, was more frequently involved in men than women, and in comparison, the head and neck region and lower limbs were more frequently affected in women, also corroborating the results from another author [10,11,15,16]. When we regarded the head and neck region alone, males had more commonly involved extrafacial part of the head and neck compared to women in both BCC and SCC lesions, similar to the findings of another study [3,4,9,10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In SCC, the head and neck accounted for a larger proportion of lesions for men than women, and the lower limbs were affected more commonly (in our series exclusively) in women, justifying literature data [3,9,15,16,27]. In BCC, the trunk, especially the back, was more frequently involved in men than women, and in comparison, the head and neck region and lower limbs were more frequently affected in women, also corroborating the results from another author [10,11,15,16]. When we regarded the head and neck region alone, males had more commonly involved extrafacial part of the head and neck compared to women in both BCC and SCC lesions, similar to the findings of another study [3,4,9,10].…”
Section: Discussionsupporting
confidence: 92%
“…Although it is generally accepted that both BCCs and SCCs develop most frequently in the head and neck region, the percentages of tumors in this body part significantly differ among analyses conducted from various countries. Most of the published documents comprising Italian [3], Slovakian [8], Brasilian [9][10][11], Portuguese [12], and Romanian [7], or Iranian [13] studies have found, the head and neck represented 73.6-96.8% of all BCCs [3,7,8,[10][11][12][13] and 70.2-77.6% of all SCCs [3,[7][8][9]12] analyzed. In this study, this body part comprised 69% of BCCs and 81.5% of SCCs diagnosed, corroborating above-mentioned papers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BCC, however, the results regard ing gender prevalence are much more controversial. While some authors [1,13,14,16] have demonstrated a higher preponderance of men, other investigators [15,18] found higher prevalence of women. In our series, a proportion of men (49.91%) and women (50.09%) affected by BCC was virtually identical.…”
Section: Resultsmentioning
confidence: 99%
“…The present data suggest that the "typical" BCC patient in northwestern Europe is becoming younger and is more often female. This inversion of prevalence may be associated with new concept of beauty, such as the "culture of tanned skin" with a ris ing demand for natural and artificial tann ing in young women [14]. Further, it could be at least partially explained by the fact that the female population is the target audience for educational campaigns against cancer, mak ing them more aware and careful about their own body [14,16].…”
Section: Resultsmentioning
confidence: 99%